Dual Roles of GSNOR1 in Cell Death and Immunity in Tetraploid Nicotiana tabacum - Li, Zhen-Chao; Ren, Qian-Wei; Guo, Yan; Ran, Jie; Ren, Xiao-Tian; Wu, Ni-Ni; Xu, Hui-Yang; Liu, Xia; Liu, Jian-Zhong (Frontiers in Plant Science, 2021)
S-Nitrosoglutathione Reductase 1 (GSNOR1) is the key enzyme that regulates cellular homeostasis of S-nitrosylation. Although extensively studied in Arabidopsis, the roles of GSNOR1 in tetraploid Nicotiana species has not been investigated previously. To study the function of NtGSNOR1, we knocked out two NtGSNOR1 genes simultaneously in N. tabacum using CRISPR/Cas9 technology. To our surprise, a natural spontaneous cell death occurred on the leaves of the CRISPR/Cas9 lines but not on that of the wildtype (WT) plants, suggesting that NtGSNOR1 negatively regulates cell death. The natural cell death on the CRISPR/Cas9 lines could be resulted from interactions between over-accumulated NO and H2O2. This spontaneous cell death phenotype was not rescued affected by knocking out two Enhanced disease susceptibility 1 genes (NtEDS11a/1b), and thus was independent of SA pathway. Unexpectedly, we found that the NtGSNOR1a/1b knockout plants displayed a significantly (p<0.001) enhanced resistance to parquat-induced cell death compared to WT plants, suggesting that NtGSNOR1 functions as a positive regulator of the paraquat-induced cell death. The increased resistance to the paraquat-induced cell death of the NtGSNOR1a/1b knockout plants was correlated with the reduced level of H2O2 accumulation (>0.95). Interestingly, whereas the N gene-mediated resistance to Tobacco mosaic virus (TMV) was significantly enhanced (p<0.001), the resistance to Pseudomonas syringae pv. tomato DC3000 was significantly reduced (p<0.01) in the NtGSNOR1a/1b knockout lines. In summary, our results indicate that NtGSNOR1 functions as both positive and negative regulator of cell death under different conditions and displays distinct effects on resistance against viral and bacterial pathogens.